The Role Of The Police In Coping With The Case Of Thuggery In The Batudaa Sub-District - Arjun Setiawan Zakaria (Estudiante Law Journal, 2019)
The implementation of this research was to find out and analyze how the role of the police in coping with thuggery cases in the Batudaa sub-district and to find out the factors that cause thuggery cases in the Batudaa sub-district. This type of research was empirical research. The results of the study showed that the role of the police in coping with thuggery cases in the Batudaa sub-district has been carried out by taking pre-emptive, preventive, and repressive actions. Meanwhile, the factors that caused the occurrence of thuggery cases in the Batudaa sub-district were the low level of public awareness due to several factors that caused the occurrence of criminal acts of thuggery, namely economic factors, understanding of the law, as well as unsupportive culture, and community environment.